Ketamine increases positive symptoms more than negative and cognitive ones: a systematic review and meta-analysis. (2nd January 2021) - Tsai, Yen-Ying; Yang, Hao-Jan
ABSTRACT: Background: Studies have confirmed that long-term use of ketamine can cause cystitis and cognitive deficits, but it remained unclear whether or not psychotic symptoms were induced as well. Therefore, we tried to analyze the correlation between ketamine and psychotic symptoms. Methods: The databases searched for this review included PubMed, Scopus, PsycINFO, and Google Scholar. The search keywords were "ketamine and (schizophrenia or psychosis)". The publication dates were between Aug 1 st, 2008 and Feb 1 st, 2018. The following inclusion criteria were used: (1) the administered medicine was S-ketamine, (2) all participants were healthy adults, (3) used the Positive and Negative Symptom Scale (PANSS) as the measurement tool and resulting test scores were the dependent variables. All studies included were clinical trials. Results: This study indicated that S-ketamine increased the PANSS total score as well as all sub-scale scores, with the greatest increase observed for positive symptoms ( t = 4.88, p <.01). We made the forest plot and meta-analysis of the positive symptom score ( Z = 7.30, p =.001) by comparing the five studies. Conclusions: S-ketamine can induce positive symptoms in a short period of time, but the severity of psychotic symptoms induced did not support a diagnosis of schizophrenia.